A Preliminary Sociolinguistic Comparison of Four Indigenous Pidgin Languages of North America ( With Notes Towards a Sociolinguistic Typology in American Indian Linguistics) - Drechsel, Emmanuel J. (My University, 1981)
This article presents a systematic sociolinguistic comparison of four indigenous pidgin languages of North America: Eskimo Jargon, Chinook Jargon, Delaware Jargon, and Mobilian Jargon. Drawing on available historical and descriptive sources, the study examines both linguistic features—such as phonology, lexicon, morphology, syntax, word order, and variability—and extralinguistic factors, including sociocultural environments, language functions, and patterns of use.
20 pgs. Typescript, letter-sized, in good condition
Keywords: Pidgin languages—North America; Sociolinguistics—North America; Indigenous languages—North America; American Indian languages; Chinook jargon; Mobilian jargon; Eskimo jargon; Delaware jargon